The Role of Technology in Enhancing Students’ Digital Literacy - Salsabila, Unik Hanifah; Maragustam, Maragustam; Murtono, Murtono (FKIP Universitas Lampung, 2024)
The Role of Technology in Enhancing Students' Digital Literacy. Objective: To ascertain the function of technology integration in augmenting digital literacy proficiency and to explore the mediating influence of heutagogy in elucidating the correlation between technology integration and digital literacy. Methods: A quantitative method was utilized to examine data from student responders in the